THE INSPECTIFY: MOBILE APPLICATION FOR SUPPORTING AIRPORT FACILITY TERMINAL INSPECTION SERVICE - Gultom, Venny Oktarina (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Operational activities at the airport are highly dependent on the efficiency and reliability of facilities, and formal reporting evidence is needed to improve the quality of facilities inspections at the Terminal Inspection Service (TIS) unit, as well as to serve as monitoring evidence that will be used as a basis for facility improvement evaluations. This study aims to design and develop the Inspectify application. The research methodology used is the Research and Development (R&D) method with the Borg and Gall research model. The study results show that the Inspectify application can facilitate the reporting process of facility damages and maintenance while improving the response to issues occurring since this application has features to track the status of repairs and receive real-time notifications. This application supported TIS personnel in conducting inspections more effectively and efficiently. Implementing this application is expected to contribute positively to airport operations, improve the efficiency of TIS personnel’s work, become the TIS data center, and increase overall passenger satisfaction.